The identification of the development stages of the karstic fracture–cavity carbonate reservoirs: a case study on the lungu oilfield, Tarim basin - Chang, Shaoying; Wang, Mengxiu (Frontiers in Earth Science, 2023)
The difficulty in identifying the connectivity of karstic fracture-cavity reservoirs hinders the efficient development of oil and gas due to the poor knowledge of the development stages and distribution of karstic reservoirs. In this paper, the layered interpretation method is used to predict the distribution of different development stages of karstic reservoirs. First, based on the knowledge that karstic formations are mainly determined by the water table, the paleomorphology would be reconstructed, and the representative wells would be selected according to the order of paleomorphology from old to new, and then the karst base level can be determined and karstic layers of single wells can be divided. Second, small-scale karstic reservoirs would be identified; And then we select the isochronous sedimentary interfaces, flatten the seismic events and map the karstic layers on wells to corresponding seismic sections, namely well-to-seismic calibration. Finally, the karstic layers would be interpreted accurately and the root-mean-square amplitudes would be extracted, and the distribution of each reservoir would be predicted. In order to demonstrate the accuracy and efficiency of this method, we applied it to fracture-cavity reservoirs in the LGX area, Tarim Basin. The result shows that 22 fracture-cavity reservoirs has been recognized based on the idea of analyzing the distribution and connectivity of karstic reservoirs, which proves that this method can contribute to the production of reservoirs in terms of efficiency and accuracy.